2016
DOI: 10.18632/oncotarget.9278
|View full text |Cite
|
Sign up to set email alerts
|

Translin and Trax differentially regulate telomere-associated transcript homeostasis

Abstract: Translin and Trax proteins are highly conserved nucleic acid binding proteins that have been implicated in RNA regulation in a range of biological processes including tRNA processing, RNA interference, microRNA degradation during oncogenesis, spermatogenesis and neuronal regulation. Here, we explore the function of this paralogue pair of proteins in the fission yeast. Using transcript analysis we demonstrate a reciprocal mechanism for control of telomere-associated transcripts. Mutation of tfx1+ (Trax) elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 57 publications
(88 reference statements)
1
13
0
Order By: Relevance
“…30 A recent report indicated that translin and TRAX differentially regulate the level of long noncoding telomeric repeat-containing RNA, however, this did not correlate to the telomere DNA damage response. 31 Given that DNA damage enhances chromatin dynamics through nucleosome degradation and promotes efficient repair, 32 the functional roles of translin and TRAX deserve further exploration.…”
Section: Roles Of Translin and Trax In Dna Damage Responsesmentioning
confidence: 99%
“…30 A recent report indicated that translin and TRAX differentially regulate the level of long noncoding telomeric repeat-containing RNA, however, this did not correlate to the telomere DNA damage response. 31 Given that DNA damage enhances chromatin dynamics through nucleosome degradation and promotes efficient repair, 32 the functional roles of translin and TRAX deserve further exploration.…”
Section: Roles Of Translin and Trax In Dna Damage Responsesmentioning
confidence: 99%
“…Of interest, the promoter of NCOA6 has been found to be depleted in H4K12ac binding sites in the human spermatozoa of subfertile patients, thus suggesting a potential altered transfer of epigenetic marks to the oocyte (Vieweg et al 2015). Similarly, the Translinassociated protein X (TSNAX) could be related to the regulation of the well-known presence of RNAs and non-coding RNAs in sperm and its deregulation in infertile males (Jodar et al 2012(Jodar et al , 2013(Jodar et al , 2015Pantano et al 2015;Gomez-Escobar et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional control of the telomere and subtelomere lncRNAs remains poorly characterized, and transcriptional activators/repressors and RNA factors binding the telomere-associated transcripts have still not been extensively studied. Recent works addressing this question showed that Translin (Tsn1) and Trax (Tfx1) proteins, two highly conserved nucleic acid-binding proteins implicated in RNA regulation, both reciprocally regulate sub- and telomeric transcripts [ 142 ]. Trax represses subtelomeric ARRET while Translin induces its transcription.…”
Section: Transcripts With Telomere-related Functionsmentioning
confidence: 99%
“…Vice versa , Translin represses TERRA transcripts whereas Trax maintains high levels of TERRA. This reveals a novel regulation mechanism of telomere-associated transcription and potential functional implications for TERRA and subTERRA in physiological contexts [ 142 ].…”
Section: Transcripts With Telomere-related Functionsmentioning
confidence: 99%